Smoking cessation for people with severe mental illness (SCIMITAR+): a pragmatic randomised controlled trial. (May 2019) - Gilbody, Simon; Peckham, Emily; Bailey, Della; Arundel, Catherine; Heron, Paul; Crosland, Suzanne; Fairhurst, Caroline; Hewitt, Catherine; Li, Jinshuo; Parrott, Steve; Bradshaw, Tim; Horspool, Michelle; et al.
Summary: Background: People with severe mental illnesses such as schizophrenia are three times more likely to smoke than the wider population, contributing to widening health inequalities. Smoking remains the largest modifiable risk factor for this health inequality, but people with severe mental illness have not historically engaged with smoking cessation services. We aimed to test the effectiveness of a combined behavioural and pharmacological smoking cessation intervention targeted specifically at people with severe mental illness. Methods: In the smoking cessation intervention for severe mental illness (SCIMITAR+) trial, a pragmatic, randomised controlled study, we recruited heavy smokers with bipolar disorder or schizophrenia from 16 primary care and 21 community-based mental health sites in the UK. Participants were eligible if they were aged 18 years or older, and smoked at least five cigarettes per day. Exclusion criteria included substantial comorbid drug or alcohol problems and people who lacked capacity to consent at the time of recruitment. Using computer-generated random numbers, participants were randomly assigned (1:1) to a bespoke smoking cessation intervention or to usual care. Participants, mental health specialists, and primary care physicians were unmasked to assignment. The bespoke smoking cessation intervention consisted of behavioural support from a mental health smoking cessation practitioner and pharmacological aids for smoking cessation, with adaptations for people with severe mental illness—such as, extended pre-quit sessions, cut down to quit, and home visits. Access to pharmacotherapy was via primary care after discussion with the smoking cessation specialist. Under usual care participants were offered access to local smoking cessation services not specifically designed for people with severe mental illnesses. The primary endpoint was smoking cessation at 12 months ascertained via carbon monoxide measurements below 10 parts per million and self-reported cessation for the past 7 days. Secondary endpoints were biologically verified smoking cessation at 6 months; number of cigarettes smoked per day, Fagerström Test for Nicotine Dependence (FTND) and Motivation to Quit (MTQ) questionnaire; general and mental health functioning determined via the Patient Health Questionnaire-9 (PHQ-9), the Generalised Anxiety Disorder-7 (GAD-7) questionnaire, and 12-Item Short Form Health Survey (SF-12); and body-mass index (BMI). This trial was registerd with the ISRCTN registry, number ISRCTN72955454, and is complete. Findings: Between Oct 7, 2015, and Dec 16, 2016, 526 eligible patients were randomly assigned to the bespoke smoking cessation intervention (n=265) or usual care (n=261). 309 (59%) participants were male, median age was 47·2 years (IQR 36·3–54·5), with high nicotine dependence (mean 24 cigarettes per day [SD 13·2]), and the most common severe mental disorders were schizophrenia or other psychotic illness (n=343 [65%]), bipolar disorder (n=115 [22%]), and schizoaffective disorder (n=66 [13%]). 234 (88%) of intervention participants engaged with the treatment programme and attended 6·4 (SD 3·5) quit smoking sessions, with an average duration of 39 min (SD 17; median 35 min, range 5–120). Verified quit data at 12 months were available for 219 (84%) of 261 usual care and 223 (84%) of 265 intervention participants. The proportion of participants who had quit at 12 months was higher in the intervention group than in the usual care group, but non-significantly (34 [15%] of 223 [13% of those assigned to group] vs 22 [10%] of 219 [8% of those assigned to group], risk difference 5·2%, 95% CI −1·0 to 11·4; odds ratio [OR] 1·6, 95% CI 0·9 to 2·9; p=0·10). The proportion of participants who quit at 6 months was significantly higher in the intervention group than in the usual care group (32 [14%] of 226 vs 14 [6%] of 217; risk difference 7·7%, 95% CI 2·1 to 13·3; OR 2·4, 95% CI 1·2 to 4·6; p=0·010). The incidence rate ratio for number of cigarettes smoked per day at 6 months was 0·90 (95% CI 0·80 to 1·01; p=0·079), and at 12 months was 1·00 (0·89 to 1·13; p=0·95). At both 6 months and 12 months, the intervention group was non-significantly favoured in the FTND (adjusted mean difference 6 months −0·18, 95% CI −0·53 to 0·17, p=0·32; and 12 months −0·01, −0·39 to 0·38, p=0·97) and MTQ questionnaire (adjusted mean difference 0·58, −0·01 to 1·17, p=0·056; and 12 months 0·64, 0·04 to 1·24, p=0·038). The PHQ-9 showed no difference between the groups (adjusted mean difference at 6 months 0·20, 95% CI −0·85 to 1·24 vs 12 months −0·12, −1·18 to 0·94). For the SF-12 survey, we saw evidence of improvement in physical health in the intervention group at 6 months (adjusted mean difference 1·75, 95% CI 0·21 to 3·28), but this difference was not evident at 12 months (0·59, −1·07 to 2·26); and we saw no difference in mental health between the groups at 6 or 12 months (adjusted mean difference at 6 months −0·73, 95% CI −2·82 to 1·36, and 12 months −0·41, −2·35 to 1·53). The GAD-7 questionnaire showed no difference between the groups (adjusted mean difference at 6 months −0·32 95% CI −1·26 to 0·62 vs 12 months −0·10, −1·05 to 0·86). No difference in BMI was seen between the groups (adjusted mean difference 6 months 0·16, 95% CI −0·54 to 0·85; 12 months 0·25, −0·62 to 1·13). Interpretation: This bespoke intervention is a candidate model of smoking cessation for clinicians and policy makers to address high prevalence of smoking. The incidence of quitting at 6 months shows that smoking cessation can be achieved, but the waning of this effect by 12 months means more effort is needed for sustained quitting. Funding: National Institute for Health Research Health Technology Assessment Programme.